Respostas

2014-07-29T20:17:27-03:00
A) -x + 8 = 5x + 36        8 -36 = 5x +x      -28 = 6x       -28/6 = x     x= -14/3

b) 6x - 16 = 2x + 16    6x - 2x = 16 + 16     4x = 32     x = 32/4    x= 8

c) -2x - 7 = -5x + 41     -2x + 5x = 41 + 7   3x = 48     x = 48/3    x = 16

d) 8x + 20 = -2x + 130     8x + 2x = 130 - 20    10x = 110    x = 110/10   x = 11

e) -3x+2x-9=-3x+21    -3x + 2x +3x = 21 + 9      2x = 30    x=30/2   x=15

f) 9 - 3x = -4x + 10      -3x + 4x = 10 - 9       x= 1    deve ter algo errado quando digitou essa equação. verifique  

g) 2x - 3 = -5x + 60       2x = 60 + 3       2X = 63      X = 63/2